1994
DOI: 10.1111/j.1365-2826.1994.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Projections from Ventrolateral Hypothalamic Neurons Containing Progestin Receptor‐ and Substance P‐Immunoreactivity to Specific Forebrain and Midbrain Areas in Female Guinea Pigs

Abstract: Many neurons within the ventrolateral hypothalamus in guinea pigs contain estrogen-induced progestin receptors as well as substance P. Retrograde tracing combined with immunocytochemistry was used to determine the specific projections of this subset of steroid-sensitive cells. Unilateral Fluoro-Gold injections into the dorsal midbrain, including the central gray, labeled a large proportion of the ventrolateral hypothalamic neurons immunoreactive for both progestin receptors and substance P (approximately 30%);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…Because the VLH was so heavily stained by the Pha-L, the quantification of ERIR cells containing Pha-Lir was not possible. However, the terminal fields observed were regions in which estrogen receptor-containing cells have been reported to project [26, 43, 48, 49, 50]. Thus, the location of projections from the VLH determined in this study using anterograde labeling is consistent with previous reports of projections of estrogen receptor-containing cells in the VLH.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Because the VLH was so heavily stained by the Pha-L, the quantification of ERIR cells containing Pha-Lir was not possible. However, the terminal fields observed were regions in which estrogen receptor-containing cells have been reported to project [26, 43, 48, 49, 50]. Thus, the location of projections from the VLH determined in this study using anterograde labeling is consistent with previous reports of projections of estrogen receptor-containing cells in the VLH.…”
Section: Discussionsupporting
confidence: 82%
“…Although differences between this experiment and previous experiments include the sex of the animals used, the particular steroid hormone receptor investigated (estrogen receptor or progestin receptor), species (rat or guinea pig), and precise hypothalamic locus studied, the studies are all in agreement with the idea that the estrogen receptor-containing neurons within the general area of the VLH project to each of these areas [26, 43, 48, 50, 51, 52, 53]. Thus, many of the estrogen receptor-containing neurons in the VLH project to those regions which also receive the heaviest projections from the VLH and also contain the largest number of boutons closely associated with ERIR cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A number of studies have suggested that SP may be an important participant in this circuitry, as SP injections in the periaqueductal central gray of OVX, estrogen-primed rats produced a long-lasting increase of lordosis behavior (Dornan et al 1987), whereas SP antiserum injections in the same region inhibit the behavior (Dornan et al 1987). Interestingly, FluoroGold injections into the dorsal midbrain labeled a large proportion (approximately 30%) of the vl VMN neurons immunoreactive for SP in the guinea pig (Ricciardi & Blaustein 1994). Furthermore, pulsatile administration of estradiol selectively induces the expression of progesterone receptors in SP neurons located in this area (Olster & Blaustein 1992), and this process is necessary for the induction of lordosis (Rubin & Barfield 1983).…”
Section: Substance Pmentioning
confidence: 99%